The True Face of Pre-Colonial Africa in “Things Fall Apart” - Bekler, Ecevit (Respectus Philologicus, 2014)
The Nigerian writer Chinua Achebe is known to be one of the most influential African writers and holds an important place in postcolonial studies. His main aim was to reconstruct the wrongly established beliefs, ideas, and thoughts of the Western world regarding Africa. To realize his aim, he made careful selections in his choice of language, which contributed greatly to sharing his observations, ideas, and beliefs with the rest of the world. He wrote his novels in English, believing that doing so would be more powerful in conveying the true face of pre-colonial Africa, rather than in Nigerian, which could not be as effective as the language of the colonizers. Achebe’s complaint was that the history of Africa had mainly been written by white men who did not belong to his continent and who would not judge life there fairly. With his novels, he changed the prejudices of those who had never been to Africa, and he managed to convert the negative ideas and feelings caused by the portrayal of his continent to positive ones. Things Fall Apart is a novel whose mission is to portray Africa in a very realistic and authentic environment, contrary to the one-sided point of view of the colonizers. The novel presents us, in very authentic language, with many details about the customs, rituals, daily life practices, ceremonies, beliefs, and even jokes of the African Igbos. Chinua Achebe thus realizes his aim in revealing that African tribes, although regarded as having a primitive life and being very far from civilization, in fact had their own life with traditions and a culture specific to themselves.